2022
DOI: 10.22270/jddt.v12i2-s.5409
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antimicrobial and Antioxidant Activities of Aloe buettneri, Mitracarpus scaber and Hannoa undulata used in Togolese Cosmetopoeia

Abstract: Background: Aloe buettneri, Mitracarpus scaber and Hannoa undulata are three plants species used in the Togolese traditional medicine to cure dermatosis. This study aims at assessing their anti-oxidant and anti-microbial activities on acne-developing micro-organisms. Methods: Six micro-organisms including Cutibacterium acnes ATCC 6919, Pseudomonas aeruginosa ATCC 27853; Escherichia coli ATCC 25922; Klebsiella pneumoniae ATCC 700603; Staphylococcus aureus ATCC 29213; and Candida albicans ATCC 35659 were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Conversely, some plants were completely inactive, while others had very high MICs, thus making them inactive. For example, the aqueous extract from leaves of Lannea microcarpa was not active in all the skin pathogens tested [134], while the leaves of Sansevieria liberica and the roots of Hannoa undulata had a MIC value of 62.5 mg/mL each [127,151]. Some of these studies have confirmed or validated the ethnobotanical use of the plants, while others did not support their use.…”
Section: Biological Activities Of the Recorded Plantsmentioning
confidence: 99%
“…Conversely, some plants were completely inactive, while others had very high MICs, thus making them inactive. For example, the aqueous extract from leaves of Lannea microcarpa was not active in all the skin pathogens tested [134], while the leaves of Sansevieria liberica and the roots of Hannoa undulata had a MIC value of 62.5 mg/mL each [127,151]. Some of these studies have confirmed or validated the ethnobotanical use of the plants, while others did not support their use.…”
Section: Biological Activities Of the Recorded Plantsmentioning
confidence: 99%
“…17 Hydroalcoholic extracts of Mitracarpus scaber,Aloe buettneri and Hannoa udulata have bactericidal and bacteriostatic properties on Cutibacterium acnes and staphylococcus aureus,two main bacteria responsible of acne. 26 Essential oils of Anthemis aciphylla obtained by hydrodistillation showed a weak to moderate inhibitory effect against S. aureus and S. Epidermidis. 27 The extracts of duzhong and yerba mate also reduced the secretion of pro-inflammatory cytokines such as TNF-α, IL-8 and IL-1β.…”
Section: Phytotherapy Of Acnementioning
confidence: 99%
“…Respectively, the Presumptive Diffusion Test (PDM) onto agar and Broth Dilution Test (BDT) [38,39] were performed to assess the Antifungal Minimum Inhibitory Concentration (MICs). The PDM was used to assess the inhibition activities of the six different concentrations, 50 mg/mL, 100 mg/mL, 150 mg/mL, 200 mg/mL, 250 mg/mL, and 500 mg/mL of Ocimum gratissimum hydroethanolic extract on Candida albicans [40].…”
Section: In Vitro Screeningmentioning
confidence: 99%